Is increased residual shank length a competitive advantage for elite transtibial amputee long jumpers? - Nolan, L.; Patritti, B. L.; Stana, L.; Tweedy, S. M. (Adapted Physical Activity Quarterly, 2011)
The purpose of this study was to evaluate the extent to which residual shank length affects long jump performance of elite athletes with a unilateral transtibial amputation. Sixteen elite, male, long jumpers with a transtibial amputation were videoed while competing in major championships (World Championships 1998, 2002 and Paralympic Games, 2004). The approach, take-off, and landing of each athlete`s best jump was digitized to determine residual and intact shank lengths, jump distance, and horizontal and vertical velocity of center of mass at touchdown. Residual shank length ranged from 15 cm to 38 cm. There were weak, nonsignificant relationships between residual shank length and (a) distance jumped (r = 0.30), (b) horizontal velocity (r = 0.31), and vertical velocity (r = 0.05). Based on these results, residual shank length is not an important determinant of long jump performance, and it is therefore appropriate that all long jumpers with transtibial amputation compete in the same class. The relationship between residual shank length and key performance variables was stronger among athletes that jumped off their prosthetic leg (N = 5), and although this result must be interpreted cautiously, it indicates the need for further research.